2008
DOI: 10.1016/j.ygcen.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A perchlorate sensitive iodide transporter in frogs

Abstract: Nucleotide sequence comparisons have identified a gene product in the genome database of African clawed frogs (Xenopus laevis) as a probable member of the solute carrier family of membrane transporters. To confirm its identity as a putative iodide transporter, we examined the function of this sequence after heterologous expression in mammalian cells. A green monkey kidney cell line transfected with the Xenopus nucleotide sequence had significantly greater (125)I uptake than sham-transfected control cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Perchlorate contamination has been reported in ground and surface waters across North America (ASTSWMO 2011; Blount et al 2010;GAO 2010;Parker et al 2008;Backus et al 2005;Reviewed in Trumpolt et al 2005) and the anion has been found to compete with iodide at the sodium-iodide symporter in the thyroid (Carr et al 2008). However, few studies have examined the effects of prolonged exposure to the thyroid hormone disrupting chemical particularly at environmentally relevant concentrations in lower vertebrates, such as amphibians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perchlorate contamination has been reported in ground and surface waters across North America (ASTSWMO 2011; Blount et al 2010;GAO 2010;Parker et al 2008;Backus et al 2005;Reviewed in Trumpolt et al 2005) and the anion has been found to compete with iodide at the sodium-iodide symporter in the thyroid (Carr et al 2008). However, few studies have examined the effects of prolonged exposure to the thyroid hormone disrupting chemical particularly at environmentally relevant concentrations in lower vertebrates, such as amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian development and growth is dependent on thyroid hormones, and thus we examined the effects of environmentally relevant concentrations of KClO 4 on thyroid hormonerelated gene expression. ClO 4 competitively inhibits the uptake of Ivia the NIS limiting the synthesis of the iodine-rich thyroid hormones (T4 and T3) by the thyroid gland (Carr et al 2008). Mukhi et al 2007;X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation